Determinants of purchase intention, satisfaction, and risk reduction: The role of knowledge and information search among mortgage buyers - N. Srinivasa Reddy; Jayanthi Thanigan (Cogent Economics & Finance, 2023)
As housing demand rose post-COVID-19, new mortgage buyers with distinct preferences are entering the market. Nevertheless, the mortgage purchasing process can prove intricate and precarious for individuals lacking familiarity. Customers leverage various online platforms and supplementary sources to augment their knowledge and mitigate perceived risks, enabling them to make well-informed decisions during the mortgage buying process. Despite exerting these efforts, customers continue to harbor unfavorable purchase intentions due to their subpar purchasing experience, leaving mortgage lenders grappling with retention issues. Research has highlighted that only 15% of mortgage transfer customers would buy a mortgage from the original provider. The present study examines mortgage purchase intention and risk reduction by integrating customer empowerment and uncertainty reduction theories to contribute to the existing literature on mortgage decision-making. A survey was conducted among 554 mortgage buyers, and PLS-SEM was used to test the hypotheses. Knowledge positively influenced satisfaction (Ø = 0.15, p= = 0.01), and satisfaction positively affected purchase intention (Ø = 0.75, p = 0.01). The mediating mechanism of risk reduction through involvement and information search is also established. The findings suggest that customers involved in decision-making and information search are more likely to be satisfied with their purchase and experience less risk. Mortgage companies should encourage customers to be more involved and provide complete information during buying. As involved customers experience less confusion; they will make sound financial decisions and remain satisfied and loyal to the mortgage company. Using behavioral finance, policymakers could provide customers necessary nudges to improve decision-making.
Keywords: 330; Involvement; Mediation; Mortgage decision-making; mortgage satisfaction; Purchase intention Knowledge; Risk-reduction